Noncontact optical 3D strain measurements in cervical soft tissues biomechanics by digital image correlation under tensile test: an experimental approach - Lin, Fangzheng; Cai, Yaoqian; Li, Jing; Zhan, Jiheng; Gao, Zibo; Zeng, Xiaolong; Feng, Minshan; Li, Yongjin; Lin, Dingkun; Qi, Ji (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundDigital image correlation (DIC) is widely used to measure surface strain in loaded objects. When studying the deformation of the cervical spine, the complexity and non-planarity of the structure complicate the speckle pattern required for applying DIC. While this non-invasive technique has shown promise in biomechanical testing, its application to cervical spine analysis presents unique challenges, particularly in achieving dynamic full-scale multi-aspect strain measurements. The aim of this paper is to introduce a method for exploring the stress-strain relationship on cervical cadaveric specimen by optical non-contact measurement system.MethodCervical cadaveric specimens were selected as subjects. Before testing, anatomical exposure, embedding, and spraying were performed sequentially. Specimen preparation was optimized through transverse process removal to enhance visualization of key anatomical structures. The surface strain under tensile testing was analyzed by the Aramis non-contact measurement system.ResultHigh-quality three-dimensional strain images were obtained with improved inspection points across all aspects, particularly in the lateral aspect (5397.25 ± 723.76 vs. 3268.25 ± 573.17, P < 0.05). Under 60N tensile loading, strain distribution revealed concentration in soft tissue regions while preserving clear visualization of vertebral bodies, intervertebral discs, and foramina. Quantitative analysis shown consistent deformation patterns across cervical segments (C4-C7), with no significant differences in segmental parameters (P > 0.05).ConclusionThe application of an optical non-contact measurement system in this study of cervical spine biomechanics has been proven effective. This method potentially mitigates some of the limitations associated with previous DIC techniques when applied to cervical cadaveric specimens. As a result, it enables more available measurements of multidimensional strain, which may enhance our understanding of the mechanics of the cervical spine.